Bargaining Agenda in a Unionized Bilateral Monopoly. (9th September 2019) - Fanti, Luciano; Buccella, Domenico
Abstract: The endogenous choice of the bargaining agenda between the two alternatives of Right‐to‐Manage (RTM, i.e., only wages are negotiated) and Efficient Bargaining (EB, i.e., both wages and employment are negotiated) is examined in a vertically integrated unionized bilateral monopoly with firm‐specific negotiations. Although the RTM agenda emerges as the unique subgame perfect equilibrium choice, a joint commitment to EB agendas leads both bilateral monopolists to gain higher profits, provided that the union bargaining power is adequately weak. This result is in sharp contrast to previous findings that the RTM typically secures higher profits to a single unionized monopolist.